DNA annealing by Redβ is insufficient for homologous recombination and the additional requirements involve intra- and inter-molecular interactions. - Subramaniam, S; Erler, A; Fu, J; Kranz, A; Tang, J; Gopalswamy, M; Ramakrishnan, S; Keller, Adrian; Grundmeier, Guido; Müller, D; Sattler, M; Stewart, AF (Scientific Reports)

Plasma-Enhanced Chemical Vapor Deposition (PE-CVD) yields better Hydrolytical Stability of Biocompatible SiOx Thin Films on Implant Alumina Ceramics compared to Rapid Thermal Evaporation Physical Vapor Deposition (PVD) - Böke, Frederik; Giner, Ignacio; Keller, Adrian; Grundmeier, Guido; Fischer, Horst (ACS Applied Materials & Interfaces)

Anisotropic metal growth on phospholipid nanodiscs via lipid bilayer expansion - Oertel, Jana; Keller, Adrian; Prinz, Julia; Schreiber, Benjamin; Hübner, René; Kerbusch, Jochen; Bald, Ilko; Fahmy, Karim (Scientific Reports)

Structural stability of DNA origami nanostructures in the presence of chaotropic agents - Ramakrishnan, Saminathan; Krainer, Georg; Grundmeier, Guido; Schlierf, Michael; Keller, Adrian (Nanoscale)

Adsorption and adhesion studies of PdSn-nanoparticles on protonated amine and carboxylic acid-terminated surfaces - Mosebach, Bastian; Bayer, Frank Markus; Fels, Carl-Christian; Voigt, Markus; Oezkaya, Berkem; Pomorska, Agata; Torun, Boray; Keller, Adrian; Grundmeier, Guido (Surface and Interface Analysis)

The Thermal Oxidation of TiAlN High Power Pulsed Magnetron Sputtering Hard Coatings as Revealed by Combined Ion and Electron Spectroscopy - Wiesing, Martin; de los Arcos de Pedro, Maria Teresa; Grundmeier, Guido (Advanced Materials Interfaces)

Electric potential screening on metal targets submitted to reactive sputtering - Corbella, Carles; Marcak, Adrian; von Keudell, Achim; de los Arcos de Pedro, Maria Teresa (Journal of Vacuum Science & Technology A: Vacuum, Surfaces, and Films)

Nitridische und oxinitridische HPPMS-Beschichtungen für den Einsatz in der Kunststoffverarbeitung (Teil 1) - Bobzin, Kirsten; Grundmeier, Guido; Brögelmann, Tobias; de los Arcos de Pedro, Maria Teresa; Wiesing, Martin; Kruppe, Nathan C. (Vakuum in Forschung und Praxis)

(Cr,Al)N/(Cr,Al)ON Oxy-nitride Coatings deposited by Hybrid dcMS/HPPMS for Plastics Processing Applications - Bobzin, K.; Brögelmann, T.; Grundmeier, G.; de los Arcos de Pedro, Maria Teresa; Wiesing, M.; Kruppe, N.C. (Surface and Coatings Technology)

Influence of O2 exposure on the interaction between CH4 and amorphous AlYB14 - Hunold, Oliver; Wiesing, Martin; de los Arcos de Pedro, Maria Teresa; Music, Denis; Grundmeier, Guido; Schneider, Jochen M. (Applied Surface Science)

Revising secondary electron yields of ion-sputtered metal oxides - Corbella, Carles; Marcak, Adrian; de los Arcos de Pedro, Maria Teresa; von Keudell, Achim (Journal of Physics D: Applied Physics)

An efficient PE-ALD process for TiO2 thin films employing a new Ti-precursor - Gebhard, M.; Mitschker, F.; Wiesing, M.; Giner, I.; Torun, B.; de los Arcos de Pedro, Maria Teresa; Awakowicz, P.; Grundmeier, G.; Devi, A. (Journal of Materials Chemistry C)
A new Ti-precursor for low-temperature PE-ALD of titanium dioxide thin films as gas barrier layers on polymer substrates.

Combined Electrochemical and Electron Spectroscopic Investigations of the Surface Oxidation of TiAlN HPPMS Hard Coatings - Wiesing, Martin; to Baben, Moritz; Schneider, Jochen M.; de los Arcos de Pedro, Maria Teresa; Grundmeier, Guido (Electrochimica Acta)

Buildup of biobased adhesive layers by enzymatically controlled deposition on the example of casein - Strube, Oliver I.; Rüdiger, Arne A.; Bremser, Wolfgang (International Journal of Adhesion and Adhesives)

Site-Specific In Situ Synthesis of Eumelanin Nanoparticles by an Enzymatic Autodeposition-Like Process - Strube, Oliver I.; Büngeler, Anne; Bremser, Wolfgang (Biomacromolecules)

Structure of n-Alkyltrichlorosilane Monolayers on Si(100)/SiO2 - Steinrück, Hans-Georg; Will, J.; Magerl, A.; Ocko, B. M. (Langmuir)

Order and Melting in Self-Assembled Alkanol Monolayers on Amorphous SiO2 - Haddad, Julia; Steinrück, Hans-Georg; Hlaing, Htay; Kewalramani, Sumit; Pontoni, Diego; Reichert, Harald; Murphy, Bridget M.; Festersen, Sven; Runge, Benjamin; Magnussen, Olaf M.; Magerl, Andreas; Deutsch, Moshe; et al. (The Journal of Physical Chemistry C)

Structural Investigations of Self-Assembled Monolayers for Organic Electronics: Results from X-ray Reflectivity - Khassanov, Artoem; Steinrück, Hans-Georg; Schmaltz, Thomas; Magerl, Andreas; Halik, Marcus (Accounts of Chemical Research)

In situ investigation of two-step nucleation and growth of CdS nanoparticles from solution - Schiener, A.; Magerl, A.; Krach, A.; Seifert, S.; Steinrück, Hans-Georg; Zagorac, J.; Zahn, D.; Weihrich, R. (Nanoscale)

Alignment of Gold Nanoparticle-Decorated DNA Origami Nanotubes: Substrate Prepatterning versus Molecular Combing - Teschome, Bezu; Facsko, Stefan; Gothelf, Kurt V.; Keller, Adrian (Langmuir)

Fundamental understanding of the corrosion and biomineralization of MgO surfaces – An in situ AFM study - Giner, Ignacio; Keller, Adrian; Grundmeier, Guido (Corrosion Science)

Low-aspect ratio nanopatterns on bioinert alumina influence the response and morphology of osteoblast-like cells - Wittenbrink, Isabel; Hausmann, Anne; Schickle, Karolina; Lauria, Ines; Davtalab, Roswitha; Foss, Morten; Keller, Adrian; Fischer, Horst (Biomaterials)

On the way to identify microorganisms in drinking water distribution networks via DNA analysis of the gut content of freshwater isopods - Mayer, Michael; Keller, Adrian; Szewzyk, Ulrich; Warnecke, Hans-Joachim (Journal of Biotechnology)

Fundamentals and Applications of Reflection FTIR Spectroscopy for the Analysis of Plasma Processes at Materials Interfaces - Grundmeier, Guido; von Keudell, Achim; de los Arcos de Pedro, Maria Teresa (Plasma Processes and Polymers)

Spectroscopic and Microscopic Investigations of Degradation Processes in Polymer Surface-Near Regions During the Deposition of SiOx Films - Mitschker, Felix; Dietrich, Jan; Ozkaya, Berkem; de los Arcos de Pedro, Maria Teresa; Giner, Ignacio; Awakowicz, Peter; Grundmeier, Guido (Plasma Processes and Polymers)

Characteristics of a propagating, self-pulsing, constricted ‘γ-mode-like’ discharge - Schröder, Daniel; Burhenn, Sebastian; de los Arcos de Pedro, Maria Teresa; Schulz-von der Gathen, Volker (Journal of Physics D: Applied Physics)

Note: Ion-induced secondary electron emission from oxidized metal surfaces measured in a particle beam reactor - Marcak, Adrian; Corbella, Carles; de los Arcos de Pedro, Maria Teresa; von Keudell, Achim (Review of Scientific Instruments)

Processing of New Materials by Additive Manufacturing: Iron-Based Alloys Containing Silver for Biomedical Applications - Niendorf, Thomas; Brenne, Florian; Hoyer, Kay-Peter; Schwarze, Dieter; Schaper, Mirko; Grothe, Richard; Wiesener, Markus; Grundmeier, Guido; Maier, Hans Jürgen (Metallurgical and Materials Transactions A)

Joining with electrochemical support (ECUF): Cold pressure welding of copper - Ebbert, Christoph; Schmidt, H. C.; Rodman, D.; Nuernberger, F.; Homberg, W.; Maier, H. J.; Grundmeier, Guido (JOURNAL OF MATERIALS PROCESSING TECHNOLOGY)
Joining metals using electrochemical support (ECUF) is a new process for cold pressure welding sheets and parts. This new process is based on an electrochemical in-line surface treatment followed by incremental pilger rolling. The ECUF process intends to cold pressure weld materials under optimized conditions. Oxide layers on metal surfaces are known to inhibit the formation of cold pressure welds. The in-line electrochemical treatment will be used to remove these surface oxides for specific engineering metals and alloys. Hence, an improved pressure weld formation at lower forces and smaller reduction ratios is expected for the electrochemically treated surfaces. Using a more flexible pressure welding process, the number of applications could be greatly improved. First tests with copper were performed to analyse the efficiency of the proposed electrochemical surface treatments. Two electrochemical treatments, the cathodic oxide-reduction and cyclovoltammetric oxide-reduction, were compared with conventional treatments (degreasing and scratch brushing) regarding their influence on the cold pressure welding process of copper. The weld strength of lap welds has been investigated as well as the necessary reduction threshold to form a weld. It was found that the electrochemical oxide reduction resulted in higher weld strength. The results of scanning electron microscopy (SEM) and energy dispersive analysis of X-rays (EDX) indicate that surface oxides were successfully removed by the electrochemical surface treatments. (C) 2014 Elsevier B.V. All rights reserved.

Nanoscale Structure of Si/SiO2/Organics Interfaces - Steinrück, Hans-Georg; Schiener, Andreas; Schindler, Torben; Will, Johannes; Magerl, Andreas; Konovalov, Oleg; Li Destri, Giovanni; Seeck, Oliver H.; Mezger, Markus; Haddad, Julia; Deutsch, Moshe; Checco, Antonio; et al. (ACS Nano)

Interface Engineering of Molecular Charge Storage Dielectric Layers for Organic Thin-Film Memory Transistors - Khassanov, Artoem; Schmaltz, Thomas; Steinrück, Hans-Georg; Magerl, Andreas; Hirsch, Andreas; Halik, Marcus (Advanced Materials Interfaces)

Tuning the molecular order of C60-based self-assembled monolayers in field-effect transistors - Schmaltz, Thomas; Khassanov, Artoem; Steinrück, Hans-Georg; Magerl, Andreas; Hirsch, Andreas; Halik, Marcus (Nanoscale)

Pseudorotational Epitaxy of Self-Assembled Octadecyltrichlorosilane Monolayers on Sapphire (0001) - Steinrück, Hans-Georg; Magerl, A.; Deutsch, M.; Ocko, B. M. (Physical Review Letters)

Molecular Processes Studied at a Single-Molecule Level Using DNA Origami Nanostructures and Atomic Force Microscopy - Bald, Ilko; Keller, Adrian (Molecules)

X-Ray Photoelectron Spectroscopy Investigations of the Surface Reaction Layer and its Effects on the Transformation Properties of Nanoscale Ti51Ni38Cu11Shape Memory Thin Films - König, Dennis; Naujoks, Dennis; de los Arcos de Pedro, Maria Teresa; Grosse-Kreul, Simon; Ludwig, Alfred (Advanced Engineering Materials)

Description of HiPIMS plasma regimes in terms of composition, spoke formation and deposition rate - de los Arcos de Pedro, Maria Teresa; Schröder, Raphael; Gonzalvo, Yolanda Aranda; Gathen, Volker Schulz-von der; Winter, Jörg (Plasma Sources Science and Technology)

Carbon nanotube growth on AlN support: Comparison between Ni and Fe chemical states and morphology - Eren, Baran; Marot, Laurent; Steiner, Roland; de los Arcos de Pedro, Maria Teresa; Düggelin, Marcel; Mathys, Daniel; Goldie, Kenneth N.; Olivieri, Vesna; Meyer, Ernst (Chemical Physics Letters)

Simultaneous characterization of static and induced magnetic fields in high power impulse magnetron sputtering discharges - Machura, P D; Hecimovic, A; Gallian, S; Winter, J; de los Arcos de Pedro, Maria Teresa (Plasma Sources Science and Technology)

Adsorption and reactivity of nitrogen atoms on silica surface under plasma exposure - Marinov, D; Guaitella, O; de los Arcos de Pedro, Maria Teresa; von Keudell, A; Rousseau, A (Journal of Physics D: Applied Physics)

Nanostructured Er2O3 Thin Films Grown by Metalorganic Chemical Vapour Deposition - Xu, Ke; Dang, Van-Son; Ney, Andreas; de los Arcos de Pedro, Maria Teresa; Devi, Anjana (Journal of Nanoscience and Nanotechnology)

Plasma-polymerized HMDSO coatings to adjust the silver ion release properties of Ag/polymer nanocomposites - Alissawi, N.; Peter, T.; Strunskus, T.; Ebbert, Christoph; Grundmeier, Guido; Faupel, F. (JOURNAL OF NANOPARTICLE RESEARCH)
In the current work, we study the silver ion release potential and the water uptake through a SiOxCyHz-polymer which is grown from the precursor hexamethyldisiloxane (HMDSO) in radiofrequency (RF) plasma. These layers were deposited on top of two dimensional (2D) ensembles of silver nanoparticles (AgNPs) with nominal thickness of 2 nm on a 20 nm RF-sputtered polytetrafluoroethylene (PTFE) thin film. The composition of the plasma-polymerized HMDSO barriers was varied by changing the oxygen flow during the polymerization process and their thickness was varied as well. Morphology and optical properties of the nanocomposites were investigated using transmission electron microscopy (TEM) and UV-Visible spectroscopy (UV-Vis), respectively. The concentration of the silver ions released from the nanocomposites after immersion in water for several time intervals was measured using inductively coupled plasma mass spectrometry (ICP-MS). Contact angle analysis and electrochemical impedance spectroscopy (EIS) measurements were also performed and results show a strong dependence of the coatings properties and their water uptake on the oxygen content in the coating films and their thickness. Plasma polymerization with increasing the oxygen flow leads to the formation of more hydrophilic thin films with a higher Ag ion release potential. Increasing the thickness of the coatings reduced the amount of the released ions and the rate of the release process was slowed down. This indicates that by tailoring the structure and the thickness of the plasma-polymerized coating films, one can tune the silver ion release properties of Ag/polymer nanocomposites.

Region-Selective Self-Assembly of Functionalized Carbon Allotropes from Solution - Wang, Zhenxing; Mohammadzadeh, Saeideh; Schmaltz, Thomas; Kirschner, Johannes; Khassanov, Artoem; Eigler, Siegfried; Mundloch, Udo; Backes, Claudia; Steinrück, Hans-Georg; Magerl, Andreas; Hauke, Frank; Hirsch, Andreas; et al. (ACS Nano)

Low-Voltage Self-Assembled Monolayer Field-Effect Transistors on Flexible Substrates - Schmaltz, Thomas; Amin, Atefeh Y.; Khassanov, Artoem; Meyer-Friedrichsen, Timo; Steinrück, Hans-Georg; Magerl, Andreas; Segura, Juan José; Voitchovsky, Kislon; Stellacci, Francesco; Halik, Marcus (Advanced Materials)

Oxygen diffusivity in silicon derived from dynamical X-ray diffraction - Will, J.; Gröschel, A.; Kot, D.; Schubert, M. A.; Bergmann, C.; Steinrück, Hans-Georg; Kissinger, G.; Magerl, A. (Journal of Applied Physics)

Electrical and optical properties of TiO2thin films prepared by plasma-enhanced atomic layer deposition - Dang, Van-Son; Parala, Harish; Kim, Jin Hyun; Xu, Ke; Srinivasan, Nagendra B.; Edengeiser, Eugen; Havenith, Martina; Wieck, Andreas D.; de los Arcos de Pedro, Maria Teresa; Fischer, Roland. A.; Devi, Anjana (physica status solidi (a))

MOCVD of tungsten nitride thin films: Comparison of precursor performance and film characteristics - Srinivasan, Nagendra B.; Thiede, Tobias B.; de los Arcos de Pedro, Maria Teresa; Rogalla, Detlef; Becker, Hans-Werner; Devi, Anjana; Fischer, Roland A. (physica status solidi (a))

Atomic layer deposition of Er2O3 thin films from Er tris-guanidinate and water: process optimization, film analysis and electrical properties - Xu, Ke; Chaudhuri, Ayan Roy; Parala, Harish; Schwendt, Dominik; de los Arcos de Pedro, Maria Teresa; Osten, H. Jörg; Devi, Anjana (Journal of Materials Chemistry C)

Transition metal nitride thin films grown by MOCVD using amidinato based complexes [M(NtBu)2{(iPrN)2CMe}2] (M=Mo, W) as precursors - Srinivasan, N.B.; Thiede, T.B.; de los Arcos de Pedro, Maria Teresa; Gwildies, V.; Krasnopolski, M.; Becker, H.-W.; Rogalla, D.; Devi, A.; Fischer, R.A. (Surface and Coatings Technology)

Target implantation and redeposition processes during high-power impulse magnetron sputtering of aluminum - Will, Andreas; de los Arcos de Pedro, Maria Teresa; Corbella, Carles; Hecimovic, Ante; Machura, Patrick D; Winter, Jörg; von Keudell, Achim (Journal of Physics D: Applied Physics)

Particle beam experiments for the analysis of reactive sputtering processes in metals and polymer surfaces - Corbella, Carles; Grosse-Kreul, Simon; Kreiter, Oliver; de los Arcos de Pedro, Maria Teresa; Benedikt, Jan; von Keudell, Achim (Review of Scientific Instruments)